2015
DOI: 10.1051/shsconf/20151500003
|View full text |Cite
|
Sign up to set email alerts
|

Experimental results using corona discharge to attempt to reproduce the Turin Shroud Image

Abstract: Abstract.It is well known that the Turin Shroud (TS) body image is not reproducible with all its peculiar features, but a great number of attempts have been made to reproduce at the same time the macro-and micro-scale properties of the double (front and back) image of the human body impressed on the most important Relic of the Christianity. The authors are convinced that among these experiments, those performed using CD (Corona Discharge) allowed to reproduce the greatest number of similarities.The experiments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…Among the hypotheses that seem most promising, there is that connected to a strong electric field that generates the so-called corona discharge. Experimental tests carried out in collaboration with Giancarlo Pesavento [20] of the Department of Industrial Engineering of Padua University (Italy) have confirmed the achievement of a good part of the Shroud's characteristics reported in the literature, although obviously not all.…”
Section: The Impossible Imagesupporting
confidence: 62%
“…Among the hypotheses that seem most promising, there is that connected to a strong electric field that generates the so-called corona discharge. Experimental tests carried out in collaboration with Giancarlo Pesavento [20] of the Department of Industrial Engineering of Padua University (Italy) have confirmed the achievement of a good part of the Shroud's characteristics reported in the literature, although obviously not all.…”
Section: The Impossible Imagesupporting
confidence: 62%
“…Imaging of the TS by a Corona Discharge may even be a by-product of the Resurrection [9], and this may be why the image cannot be technically reproduced or scientifically explained in a complete form. By means of the present URP some progress about these hypotheses has nevertheless been obtained [28].…”
Section: -P4mentioning
confidence: 84%
“…The most probable source of energy is of electric type and connected to the Corona Discharge [9,27]. Some experiments have been performed to reproduce the TS body image and some interesting results have been recently published [28]. F. Lattarulo presents in this issue, an electrostatic hypothesis that could have produced the image.…”
Section: The Body Image Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, reproducing an integral TSM results in a purely theoretical expectation [10]; x low-powered d.c. high-voltage systems on one hand allow entire TSM-like imprinting to be obtained with fairly good reproduction of micro-scale features and with a reasonably lowenergy consumption; on the other, the image looks cylindrically distorted and impressed on the outer, instead of the inner, side of the piece of fabric corresponding to the TSM frontal region. Furthermore, the dorsal image has not been obtained so far [11].…”
Section: Introductionmentioning
confidence: 99%